The platform discount: Addressing unpaid work as a structural feature of labour platforms - Mangan David; Muszyński Karol; Pulignano Valeria (Sage, 2025)
Digital labour platforms are able to structure work to limit paid working time, extract fees from workers to access labour, and shift costs associated with occupational safety and health (OSH) compliance onto platform workers. We call this unpaid work the ‘platform discount’. Unpaid labour is embedded within platforms’ competitive strategies as platforms operate with labour oversupply while clients use multiple platforms to search for the cheapest option (multi-homing effect). The authors study pathways through law that would limit the incidence of unpaid work by revisiting three areas of the legal framework: working time, safety and health, and access to work/labour intermediation. The authors argue that reclassification, suggested, among others, by the draft Platform Work Directive, can reduce the platform discount for the misclassified workers, but will leave solo self-employed unprotected. The authors explore two possible strategies to reduce the platform discount for the solo self-employed working on labour platforms: 1) a broader understanding of the concept of working conditions on digital labour platforms covering both standard employees and solo self-employed; 2) proceeding area by area, with the extension of occupational safety and health to the solo self-employed on digital labour platforms being the most feasible and promising from a regulatory standpoint.